(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The effect of waiting line management strategies as dimensioned by perceived waiting time, customers’ engagement, staff empathy and waiting environment on positive word of mouth is the focal point of this paper. To achieve this purpose, four research questions were posed; with four corresponding hypotheses tested. The cross-sectional variant of the survey design was adopted for the study; and data was fetched from 384 customers from 15 major quick service restaurants in Rivers State. The data for the study was subjected to statistical analysis using Partial Least Square Structural Equation Modelling aided by SMART PLS. The results indicated that there is a significant relationship between waiting line management and positive word of mouth. It was demonstrated that staff empathy, perceived waiting time, customer engagement and waiting environment all had positive correlations with positive word of mouth with beta (β) values of 0.652, 0.687, 0.491 and 0.428 respectively. It was recommended that Quick service restaurants should integrate innovative technology such as online delivery systems; virtual queuing and the use of mobile apps to enable their customers make orders online rather than visiting the outlets. They should also provide serene and comfortable waiting area for on-site customers to enable them feel relaxed during their waiting periods. They were also urged to train and motivate employees to interact with customers in a friendly manner and create friendly organizational climate that would stimulate empathy as part of their organizational culture.